Optimisation of dose distribution for linear accelerator-based stereotactic radiosurgery - Suh, T. -S.; Bova, F.; Yoon, S. C.; Shinn, K. S.; Bahk, Y. W. (Medical & biological engineering & computing, 1993)
The work presented in the paper addresses a method for obtaining the optimal dose distribution for LINAC-based stereotactic radiosurgery. As many targets have nonspherical or irregular shapes and three-dimensional dose calculations included in dose optimisation, long computation times are required to determine the optimum isocentre separation and collimator sizes to shape the irregular target using the multiple-isocentre approach, by trial-and-error types of method. The simple approach, using a computer-aided design optimisation technique and a fast approximate dose model, has been developed to find the optimum isocentre positions and collimator sizes quickly and automatically. A spherical dose model has been developed to represent the dose for a standard arc system with a single isocentre. The implementation of computer-aided design algorithms with the spherical dose model and their application to several cases are discussed. It is shown that the spherical dose model gives dose distribution similar to that of the exact dose model, which makes this simple dose model more efficient, with computer-aided design optimisation, in finding optimum isocentre positions and collimator sizes used in stereotactic radiosurgery.